Effects of electrostimulation and plyometric training program combination on jump height in teenage athletes - Martinez-Lopez, E. J.; Benito-Martinez, E.; Hita-Contreras, F.; Lara-Sanchez, A.; Martinez-Amat, A. (Journal of Sports Science & Medicine, 2012)
The purpose of this study was to examine the effects of eight- week (2 days/week) training periods of plyometric exercises (PT) and neuromuscular electrostimulation (EMS) on jump height in young athletes. Squat jump (SJ), counter movement jump (CMJ) and drop jump (DJ) were performed to assess the effects of the training protocols 98 athletes (100 & 200m and 100m & 110m hurdles) voluntarily took part in this study, 51 males (52%) and 47 females (48%), 17.91 ± 1.42 years old, and 5.16 ± 2.56 years of training experience. The participants were randomly assigned to four different groups according to the frequency and the timing of the stimulation. Analysis of covariance was used to analyze the effects of every training program on jump height. Our findings suggest that compared to control (Plyometrics (PT) only), the combination of 150Hz EMS + PT simultaneously combined in an 8 week (2days/week) training program, we could observe significant jump height improvements in the different types of strength: explosive, explosive-elastic, and explosive-elastic-reactive. The combination of PT after < 85 Hz EMS did not show any jump height significant increase in sprinters. In conclusion, an eight week training program (with just two days per week) of EMS combined with plyometric exercises has proven useful for the improvement of every kind of vertical jump ability required for sprint and hurdles disciplines in teenage athletes.